Detection and Identification of Ehrlichia, Borrelia burgdorferi Sensu Lato, and Bartonella Species in Dutch Ixodes ricinus Ticks - Schouls, Leo M. (American Society for Microbiology, 1999)
A sensitive and specific PCR hybridization assay was developed for the simultaneous detection and identification of Ehrlichia and Borrelia burgdorferi sensu lato. In separate assays the 16S rRNA gene of Ehrlichia species and the 23S-5S rRNA spacer region of B. burgdorferi sensu lato were amplified and labeled by PCR. These PCR products were used in a reverse line blot hybridization assay in which oligonucleotide probes are covalently linked to a membrane in parallel lines. Hybridization of the samples with the oligonucleotide probes on this membrane enabled the simultaneous detection and identification of Ehrlichia, B. burgdorferi, and Bartonella species in 40 different samples. The application of the assay to DNA extracts from 121 Ixodes ricinus ticks collected from roe deer demonstrated that 45% of these ticks carried Ehrlichia DNA. More than half of these positive ticks carried species with 16S rRNA gene sequences closely related to those of E. phagocytophila and the human granulocytic ehrlichiosis agent. The majority of the other positive ticks were infected with a newly identified Ehrlichia-like species. In addition, 13% of the ticks were infected with one or more B. burgdorferi genospecies. In more than 70% of the ticks 16S rRNA gene sequences for Bartonella species or other species closely related to Bartonella were found. In five of the ticks both Ehrlichia and B. burgdorferi species were detected.